The relationships between teacher presenteeism, emotional demands, trust in principal and emotional exhaustion: A multilevel moderated mediated analysis - Uslukaya, Alper; Demirtas, Zulfu (Springer, 2023)
This study aims to analyze a moderated mediation model using the Job Demands-Resources model in order to test the mediation role of emotional exhaustion in the relationship between emotional demands in schools and teacher presenteeism, and moderator role of trust in principal in this mediation process. Using data from a sample of 796 teachers working in 87 schools (M = 9.149, SD = 0.347), this study used multilevel structural equation modelling with Bayesian estimaton to astimate the structural relationships between emotional demands, trust in principal, emotional exhaustion and presenteeism. The results show that emotional demands have an indirect relationship with presenteeism by promoting emotional exhaustion. This study also reveals the findings that there is an indirect relationship between emotional demands and presenteeism through emotional exhaustion depends on the level of trust in principal. Finally, we discuss the implications for practitioners and researchers.
Keywords: Job demands-resources model; Emotional demands; Emotional exhaustion; Trust in principal; Teacher presenteeism